Markers of Proliferative Diabetic Retinopathy - V. A. Biletskaya; D. V. Lipatov; I. Yu. Sayapina; M. A. Frolov; V. K. Surguch (Oftalʹmologiâ, 2022)
The incidence of diabetes mellitus (DM) is steadily growing and today the World Health Organization (WHO) describes this situation as an epidemic. Diabetic retinopathy (DR) is one of the most common complications of DM, as well as one of the main causes of acquired irreversible vision loss. Nowadays the pathogenesis of proliferative DR remains completely unexplored, but many authors think about the important role of biologically significant mediators of this process cytokines and growth factors. Cytokines and growth factors are protein mediators that regulate various functions, both locally and systemically. They carry out the cells’ life cycle, the processes of proliferation, participate in the regulation of the protective inflammatory response of the body, control angiogenesis and other mechanisms. It is proved that the main links in the pathogenesis of DR are oxidative stress, thickening of the endothelial basement membrane in capillaries, loss of pericytes, end products of glycation and inflammation. Chorioretinal hypoxia and ischemia play a major role in the formation of newly formed vessels. Newly formed vessels are defective (with a thin wall devoid of pericytes), often lead to hemorrhages, hypoxia, which in turn closes the pathological circle and causes the production of cytokines and vasoproliferative factors. Frequent complications of DR are intraocular hemorrhages, retinal fibrosis and pathological changes in the posterior hyaloid membrane, traction retinal detachment, etc. This review examines some types of cytokines and growth factors and their role in the light in the pathogenesis of proliferative DR. Modern technologies make it possible to conduct effective studies of intraocular fluids to study the content of biologically active substances both in the moisture of the anterior chamber of the eye and in the vitreous body. To narrow the scope of the review on the subject attention is focused on the works that examined various markers locally in the intraocular fluids in patients with DM. It is worth noting that there are few such studies and their results often differ significantly from each other. This fact is a subject for discussion and encourages further study of this topic.